Mass Culture of Subanguina picridis and Its Bioherbicidal Efficacy on Acroptilon repens - Ou, X. (Society of Nematologists, 1993)
A Russian knapweed (Acroptilon repens) shoot culture system, initiated from shoot tip culture, was used to generate a source of host plant tissue for the rearing of the nematode Subanguina picridis, a biocontrol agent for Russian knapweed. Young shoots growing on solid B5G medium in petri dishes developed galls on leaves, petioles, and shoot tips 7 days after release of 50 nematodes onto the surface of the medium. After 3 months of culturing, each petri dish yielded 7,000-10,000 nematodes. In vitro cultured Subanguina picridis were virulent on greenhouse-grown Russian knapweed plants. Galls were first found on seedlings 12 days after infestation; after 2 months, 90% of seedlings were galled on leaves, petioles, and shoot tips, with 1-6 galls per seedling. Three months after shoot emergence, 64% of vegetative shoots originating from root segments were also galled by the cultured nematodes. Similarly, vegetatively regenerated shoots of Russian knapweed were also susceptible to infestation by cultured nematodes.